2017
DOI: 10.1080/17429145.2017.1298853
|View full text |Cite
|
Sign up to set email alerts
|

Spodoptera exigua modulates gossypol biosynthesis in cotton Gossypium hirsutum

Abstract: Cotton plants induce high levels of gossypol in response to herbivore damage. However, little is known about the mechanisms by which insect herbivory modulates gossypol biosynthesis in cotton plants. Here, we report the mechanism by which herbivore damage or insect-originated elicitors modulate the biosynthesis of gossypol and jasmonic acid (JA) in plants. Spodoptera exigua larval-damaged (HD) cotton plants and mechanically damaged plants treated with S. exigua oral secretion (MDOS) showed higher levels of gos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Our findings also indicated no effect of leaf damage on terpenoid gland density which also agrees with a previous study of ours with wild cotton suggesting this trait has low plasticity (Abdala‐Roberts, Pérez‐Niño, Moreira, et al, 2019). However, terpenoid concentrations are thought play a key role in cotton induced resistance to insect herbivory (Chen, Schmelz, Wäckers, & Ruberson, 2008; McAuslane & Alborn, 1998; Wu, Chen, Ge, & Sun, 2007; Zebelo, Disi, Balusu, Reeves, & Fadamiro, 2017), and previous studies have reported increased gland density in response to herbivory in cultivated cotton (McAuslane et al., 1997; Opitz et al., 2008). Interestingly, a previous study with cultivated cotton found that increased terpenoid concentrations can be achieved not only by increasing the number of glands but also increasing the filling of individual glands (Opitz et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also indicated no effect of leaf damage on terpenoid gland density which also agrees with a previous study of ours with wild cotton suggesting this trait has low plasticity (Abdala‐Roberts, Pérez‐Niño, Moreira, et al, 2019). However, terpenoid concentrations are thought play a key role in cotton induced resistance to insect herbivory (Chen, Schmelz, Wäckers, & Ruberson, 2008; McAuslane & Alborn, 1998; Wu, Chen, Ge, & Sun, 2007; Zebelo, Disi, Balusu, Reeves, & Fadamiro, 2017), and previous studies have reported increased gland density in response to herbivory in cultivated cotton (McAuslane et al., 1997; Opitz et al., 2008). Interestingly, a previous study with cultivated cotton found that increased terpenoid concentrations can be achieved not only by increasing the number of glands but also increasing the filling of individual glands (Opitz et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, mechanical damage occurred only at the beginning of the experiment, whereas DBM‐damaged plants had constant pressure from the herbivore. There could be a difference in hormone levels or defensive compounds in plants that are fed on by caterpillars compared to those that simply receive mechanical damage (Zebelo et al., ). Both, herbivory and mechanical damage to nicotine plants, Nicotiana sylvestris Speg.…”
Section: Discussionmentioning
confidence: 99%
“…In cotton, inducible terpenoids play an important role and plants that do not produce these terpenoids are less resistant against herbivores and pathogens [6, 23], therefore, maintaining this resistance trait is also highly important for the long-term success of ULGCS cotton. Herbivore damage in cotton plants increases the abundance of terpenoids and other relevant resistance traits, which has a negative impact on herbivores [24]. While previous studies have looked into the terpenoid-based resistance mechanisms of ULGCS cotton, they have not addressed the impact of the trait on plant-insect interactions.…”
Section: Discussionmentioning
confidence: 99%